PERAMALAN EKSPOR MIGAS BERBASIS EKSTRAPOLASI POLINOMIAL CHEBYSHEV: Forecasting of Oil and Gas Exports Based on Chebyshev Polynomial Extrapolation - Sabina, Sabna Zulfaa; Rahmi, Dhea Wasila; Awwaliyah, Razma Rizqiyyah; Robbaniyyah, Nuzla Af’idatur; Rusadi, Tri Maryono (Al-Aqlu: Jurnal Matematika, Teknik dan Sains, 2025)
Exports play a strategic role in supporting the country's revenue. The oil and gas sector, as one of Indonesia's primary natural resources, contributes significantly to national economic growth. Indonesia's oil and gas production currently exhibits an unstable trend, influenced by the dynamics of global prices and demand. This research aims to forecast Indonesia's oil and gas export volume in 2025 using the Chebyshev extrapolation method. The Chebyshev extrapolation method is chosen due to its ability to produce more accurate predictions for data outside the available time range. The data used includes monthly export volumes of the oil and gas sector from 2019 to 2024. In the analysis, a fourth-degree Chebyshev polynomial is applied to project future export trends. The Mean Absolute Percentage Error (MAPE) for the Chebyshev extrapolation model is 12,10%. The forecasting results indicate an increase in monthly oil and gas exports in 2025, with the lowest value recorded in January at 1.373,70 and the peak export in December at 1.805,33. Overall, this prediction indicates the stability of oil and gas export volumes with a tendency towards an increasing trend compared to the previous year.